Chronological Thinking at Preschool Period: A Case Study - Kibar Aktın; Dursun Dilek (Sakarya University, 2016)
This study aims to explore early childhood chronological thinking skills and to inquire how children use these skills. Sample of the study consisted of 12 children aged 4,5-6 who attended preschool in the academic year of 2012-2013. This is a qualitative research that use case study design. Research data consisted of visual timeline documents that children created and interview recordings of children about the timeline. Data were analyzed using descriptive and content analyses. It is found that children aged between 4.5 and 6 showed success in the chronological sequences above the average. In general,it was observed that when children used chronological thinking, they made inferences partly through thinking intuitively and/or associatively based on properties and colors of the materials to determine the materials that belong to the most distant time in relation to "cause and effect" ; when determining materials that belong to the more recent past, they used historical places that they visited and older people as references; when arranging the materials that belong to the most recent time in a chronological order, they associated this order with the properties of the materials or their own daily experiences in relation to "cause and effect".